2015
DOI: 10.1007/978-3-658-08844-6_65
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of urea-water sprays in selective catalytic reduction (SCR) systems

Abstract: Urea-SCR (selective catalytic reduction) is currently the state-of-the-art NOx reduction technique for Diesel engines. The main challenges for the implementation of mobile urea-SCR systems include rapid decomposition and homogeneous distribution of urea and the mitigation of deposit formation. A key affecting these performance factors is the injection of the urea-water solution (UWS). However, urea-water sprays under exhaust flow conditions have not been studied extensively so far.The present study is a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This can be detrimental for the SCR systems operation. In [32] we have shown that the local cooling effect is strong, while under certain low conditions the local wall temperature fells below 100°C leading to permanent liquid ilm formation.…”
Section: Spray Contours Analysismentioning
confidence: 88%
See 3 more Smart Citations
“…This can be detrimental for the SCR systems operation. In [32] we have shown that the local cooling effect is strong, while under certain low conditions the local wall temperature fells below 100°C leading to permanent liquid ilm formation.…”
Section: Spray Contours Analysismentioning
confidence: 88%
“…Based on extensive investigations [28,32] we can conclude that the sprays from pressure-driven injectors are hitting the opposed wall always at the same location, regardless of the low properties.…”
Section: Spray Contours Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…The wall surface conditions may also be used as a parameter to help the urea droplets break apart and become finer droplets [45][46][47]. Spray-wall impingement occurs as a result, and spray cooling occurs throughout the injection period [48][49][50][51]. Spray cooling creates a liquid film which is the precursor to the formation of solid deposits [52,53].…”
Section: Introductionmentioning
confidence: 99%